DNA Curtains and Nanoscale Curtain Rods: High-Throughput Tools for Single Molecule Imaging - Fazio, Teresa (2008)
Single molecule visualization of protein–DNA complexes can reveal details of reaction mechanisms and macromolecular dynamics inaccessible to traditional biochemical assays. However, these techniques are often limited by the inherent difficulty of collecting statistically relevant information from experiments explicitly designed to look at single events. New approaches that increase throughput capacity of single molecule methods have the potential for making these techniques more readily applicable to a variety of biological questions involving different types of DNA transactions. Here we show that nanofabricated chromium barriers, which are located at strategic positions on a fused silica slide otherwise coated with a supported lipid bilayer, can be used to organize DNA molecules into molecular curtains. The DNA that makes up the curtains is visualized by total internal reflection fluorescence microscopy (TIRFM) allowing simultaneous imaging of hundreds or thousands of aligned molecules. These DNA curtains present a robust experimental platform portending massively parallel data acquisition of individual protein–DNA interactions in real time.